The effects of fenfluramine on blood and tissue serotonin (5-hydroxytryptamine) levels in rats - Pirinçci, I; Atessahin, A; Karahan, I (Tubitak Scientific & Technological Research Council Turkey, 2005)
The aim of this study was to investigate the effect of fenfluramine (FEN) administered at single and repeated doses on brain, stomach and plasma serotonin (5-Hydroxytryptamine, 5-HT) levels in rats. FEN was injected intraperitoneally at single doses (1, 3 and 10 mu mol kg(-1)) and given orally at repeated doses (1.25, 5 and 10 mg kg(-1)) for 21 days. The tissues and plasma samples were collected 20, 40, 80 and 160 minutes after the single dose administrations and 4 h after the last dose administration in repeated experiments. In addition, the rats treated with the dose of 1.25 mg kg(-1) were maintained until 2 and 8 weeks and the tissues were taken at these times. The 5-HT levels in the tissue and plasma were measured by using high performance liquid chromatography (HPLC). The levels of brain 5-HT were decreased at the single FEN doses when compared with the control group. At the repeated experiments, although no effect was observed at the dose of 1.25 mg kg-1; decreases were determined in brain 5-HT levels at the high doses. The levels of 5-HT in the stomach were found to increase in both single and repeated administrations. Decreases in levels of plasma 5-HT were determined in all experimental groups. In conclusion, while fenfluramine was determined to decrease brain and plasma 5-HT levels generally, it increased the levels of stomach 5-HT.
Keywords: fenfluramine; rat; brain; stomach; plasma; serotonin